(untitled) - Grosz, Bernard (New York, NY., 2003)
The Access Language series provides an innovative, modern course for adult language learners of all ages. Whether the reader is learning for business, for pleasure, or toward an examination, these high-impact, full-color guides provide beginners with a thorough grounding in the skills required to understand, speak, read, and write contemporary French and German.
Keywords: French language,French language; Textbooks for foreign speakers,Textbooks for adults